ALTERNATIF PENYELESAIAN SENGKETA ARBITRASE INTERNASIONAL BAGI PERUSAHAAN MULTINASIONAL - Shanti Prameswari, Ni Gusti Nyoman; Pemayun, C.I.A (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
International arbitration shall be defined as dispute settlement with the existence of a neutral third party. Several arbitrations are designed in certain institutional basis while several are designed in ad hoc basis. Problem appeals when the circumstances of the conflict occurred amongst multinational corporations. It is observed that the party tend to enter the lawsuit to national court in spite of the arbitration dispute settlement. This writing shall utilize normative legal research. It is also found that, through literature-bases research, arbitration system offers more positive exerts namely a faster and less expensive mechanism, confidential, and final and binding verdicts. As seen from practical point of view, the legal effect of the verdict shall be relinquished as the absence of the good will of one party to undergo the means of verdict. Thus, international arbitration shall be considered as alternative in settling dispute among multinational corporation.
Keywords: Alternative, Dispute Settlement, International Arbitration, Multinational Corporation